USE OF ARTIFICIAL INTELLIGENCE IN MARENTING: PERSPECTIVES, ADVANTAGES AND DISADVANTAGES - Bilyk , I.I.; Lavryk , K.R. (The actual problems of regional economy development, 2023)
The article examines the impact of artificial intelligence on marketing development, including the changes it brings and how it enhances the efficiency of marketing processes. The benefits of utilizing artificial intelligence to improve marketing strategies are described, with a notable advantage being the ability of smart technologies to quickly analyze large volumes of data and provide accurate results. The latest research and publications on this topic are analyzed to provide readers with a clearer understanding of the prospects of marketing development with the use of artificial intelligence. Consequently, it was discovered that artificial intelligence can significantly facilitate and enhance the work of marketers in areas such as marketing process automation, personalized communication with clients, optimization of advertising campaigns, demand forecasting, detailed analysis of target audience preferences and past experiences, budget allocation across different channels, and content creation, among others. Special attention is given to personalized marketing, which is crucial in today's demanding consumer landscape. Artificial intelligence is becoming extremely important for achieving success and allows companies to apply a personalized approach to customers and interact with them based on analysis of their behavior. Additionally, the article discusses potential challenges and risks associated with using artificial intelligence in marketing. The possibility of errors in the work of algorithms of smart technologies and insufficiently ethical aspects of the use of data, which are related to the confidentiality and privacy of consumers, are pointed out. It is important to understand these challenges and develop appropriate strategies to address them and minimize the negative impact. In general, the use of smart technologies allows marketers to focus on strategic tasks and achieve better results with less effort and cost. And the implementation of artificial intelligence in marketing strategies is an indispensable condition for enterprises seeking to maintain their competitiveness.